2012
DOI: 10.1017/s0007114512002851
|View full text |Cite
|
Sign up to set email alerts
|

Long-term vitamin D3 supplementation is more effective than vitamin D2 in maintaining serum 25-hydroxyvitamin D status over the winter months

Abstract: Public health recommendations do not distinguish between vitamin D 2 and vitamin D 3 , yet disagreement exists on whether these two forms should be considered equivalent. The objective of the present study was to evaluate the effect of a daily physiological dose of vitamin D 2 or vitamin D 3 on 25-hydroxyvitamin D (25(OH)D) status over the winter months in healthy adults living in Dunedin, New Zealand (latitude 468S). Participants aged 18-50 years were randomly assigned to 25 mg (1000 IU) vitamin D 3 (n 32), 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
97
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 16 publications
(28 reference statements)
10
97
0
1
Order By: Relevance
“…Vitamin D supplementation using ergocalciferol was the current approach at project site among liver transplant providers. The move towards cholecalciferol was appropriate given the evidence that it has shown to improve serum levels more effectively than ergocalciferol (Logan et al, 2013;Mangoo-Karim et al, 2015;Osborn & Germann, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D supplementation using ergocalciferol was the current approach at project site among liver transplant providers. The move towards cholecalciferol was appropriate given the evidence that it has shown to improve serum levels more effectively than ergocalciferol (Logan et al, 2013;Mangoo-Karim et al, 2015;Osborn & Germann, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Although both pre and post transplanted patients receive supplementation, this study focused only on the post-transplanted patient's response to this dosing schedule. This protocol replaces the previously used vitamin D2 (ergocalciferol) dosing as evidence shows the superiority of cholecalciferol in improving serum 25(OH)D levels (Logan et al, 2013;Osborn & Germann, 2011).…”
Section: Problem Statementmentioning
confidence: 99%
“…The lower affinity of 25(OH)D 2 for vitamin D binding protein relative to 25(OH)D 3 means its free fraction in blood is likely to be higher, consistent with the faster turnover of 25(OH) D 2 (8,27) . The shorter circulating half-life of ergocalciferol metabolites may lead to up-regulation of enzymes that not only metabolise ergocalciferol, but also concomitantly induce accelerated catabolism and clearance of 25(OH)D 3 (8,11) . Differential specificities of the various cytochrome P450 (CYP) enzymes that metabolise vitamin D may also help to explain the apparent effect of ergocalciferol on 25(OH)D 3 concentration.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent research has indicated that vitamin D 2 has a lesser effect on raising total vitamin D (25(OH)D) status compared to vitamin D 3 and could result in a decrease in 25(OH)D 3 concentrations (2)(3)(4) . Furthermore, only vitamin D 3 and not vitamin D 2 has been found to decrease all-cause and cancer mortality (5) .…”
mentioning
confidence: 99%
“…Furthermore, only vitamin D 3 and not vitamin D 2 has been found to decrease all-cause and cancer mortality (5) . The objective was to conduct a systematic review and meta-analysis of randomized controlled trials (RCTs) that have supplemented with vitamin D 2 via a tablet/capsule or via a food fortification vehicle, and to compare concentrations of measured serum 25(OH)D 3 following supplementation.…”
mentioning
confidence: 99%